Benthic Invertebrates on the Move: A Tale of Ocean Warming and Sediment Carbon Storage. (20th January 2023) - Bianchi, Thomas S.; Brown, Craig J.; Snelgrove, Paul V. R.; Stanley, Ryan R. E.; Cote, David; Morris, Corey
Abstract: Ongoing effects of climate change create a dual challenge of shifting distributions of organisms and concerns about the fate of organic carbon in nature. Marine sediments store vast amounts of organic carbon, but the fate of that material hinges on the biology of organisms associated with the seafloor and how they influence rates of carbon decomposition and burial. Shifts in large megafauna that disturb and thus help to oxygenate sediments could have important ramifications regarding whether sediments release or store carbon for long periods of time. We consider snow crab and lobster, two commercially important seafloor species in the Northeastern Atlantic, and the potential effects of ongoing changes in their distributions and that of their fisheries for future climate scenarios. These ongoing biogeographic shifts, considered in tandem with areas of seabed legislatively protected from fishing impacts and thus not confounded by cumulative effects of fishing gear disturbance, offer an opportunity to study how newly arrived species that disturb large areas of the seafloor might influence the global carbon cycle.